Consumption of Food Components of the Mediterranean Diet Decreases the Risk of Breast Cancer in the Makkah Region, Saudi Arabia: A Case-Control Study - Azzeh, Firas S.; Hasanain, Deena M.; Qadhi, Alaa H.; Ghafouri, Khloud J.; Azhar, Wedad F.; Ghaith, Mazen M.; Aldairi, Abdullah F.; Almasmoum, Hussain A.; Assaggaf, Hamza M.; Alhussain, Maha H.; Alghamdi, Ahmad A.; Habibullah, Mahmoud M.; et al. (Frontiers in Nutrition, 2022)
Background: Breast cancer is one of the leading causes of death worldwide, it affects both males and females. In Saudi Arabia, breast cancer has been the most prevalent type of cancer in females, for the past few years. Dietary habits and cultural beliefs vary according to region, and further studies are required to demonstrate the relationship between these dietary habits and cultural beliefs and the risk of developing breast cancer. This study aims to discover the relationship between preventative dietary factors of the Mediterranean diet and rates of breast cancer among postmenopausal females in the Makkah region of Saudi Arabia. Methods: A case-control study was conducted in King Abdulla Medical City hospital, Makkah, Saudi Arabia, and included 432 Saudi female participants: 218 in the control group and 214 breast cancer patients. All participants were postmenopausal, around the same age, and all were ethnically Arab Saudis. Data was obtained using a self-administered validated questionnaire. Results: Study results showed that a diet including 1-2 servings of legumes weekly, 1-5 servings of fish weekly, 1-5 servings of dairy products daily, 3-5 servings of fruits and vegetables daily, and more than one cup of black tea and coffee per day significantly (p<0.05) reduced the risk of breast cancer. Conclusion: This study demonstrates that consuming a Mediterranean diet, which includes legumes, fish, fruits and vegetables, black tea, and coffee as well as low intake of dairy products, works as a preventative factor against breast cancer in postmenopausal females from the Makkah region.